PEMANFAAT AN LIMBAH lKAN DALAM RANSUM UNTUK MENINGKATKAN PENDAPATAN PETANI PETERNAK AYAM BROILER DI DAERAH TEPUS, GUNUNG KIDUL, DIY - Astuti, Astuti (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2003)
This  society  servitude   aims  to use  the  fish  waste  in poultry  feed  to  increase  the income  of fishermen  in Baron,  Tepus,  Gunung  Kidul,  DIY. This purpose  is designed  into two  activities   namely,  information   delivery  about  the  idea  and  advantages   of using  the fish  waste;   and  the  process   of  manufacturing    the  fish  waste   into  fish  flour   is  also introduced.Thirty    fisherman    joined    with   this   program.    The   information    delivery    was conducted   on  21  August  2002  and  the  pratical  work  of  manufacturing    fish  flour  was conducted   on  21 November   2002  and  at Baron  meeting  house,  Tepus,  Gunung  Kidul, DIY.Result  shows  that  the  participants   show  positive  response   by  collecting   the  fish waste and drying them up, the dry fish waste then blended  to produce  the fish flour.Key words:  fish waste, poultry   feed